Defining Risk Hepatitis A Virus in Philippine Shellfish (Oyster and Mussels) - Rustia, Abigail S.; Lopez, Crisanto M.; Barrios, Erniel B.; Tanay, Dennis D.; Lagazon, Patricia Mae M.; Gosilatar, John Carlo G.; Dalmacio, Leslie Michelle M. (2024)
The hepatitis A virus (HAV) endemicity in the Philippines ranges from moderate to high.
Despite this, health risks related to local seafood consumption are associated with red tide or mass fish kill. However, government agencies should consider the safety of local shellfish and culture sites to HAV. This article examines the current trends relevant to the presence of HAV along the local shellfish supply chain – including production levels, microbial concentration, consumer behavior, and food safety regulations. Despite the susceptibility of local shellfish to HAV, the study identified crucial data gaps: [1] reliance on bacterial indicators, [2] absence of monitoring records for HAV concentration in local shellfish products and culturing sites, and [3] limited studies regarding the effect of local cooking practices on HAV inactivation. The synthesis of this analysis will guide the national food safety risk managers in addressing the identified data gaps to facilitate a full-blown food risk analysis of HAV in Philippine shellfish.
Keywords: Hepatitis A; Hepatitis; Magallana bilineata; Mussels; Oysters